Together Against COVID-19 Concerns: The Role of the Dyadic Coping Process for Partners’ Psychological Well-Being During the Pandemic - Donato, Silvia; Parise, Miriam; Pagani, Ariela Francesca; Lanz, Margherita; Regalia, Camillo; Rosnati, Rosa; Iafrate, Raffaella (Frontiers in Psychology, 2021)
The situation caused by the COVID-19 has been representing a great source of concern and a challenge to the psychological well-being of many individuals around the world. For couples in particular, this extraordinary rise in concern, combined with the stress posed by the virus containment measures, such as prolonged cohabitation and lack of support networks, may have increased the likelihood of couple problems. At the same time, however, COVID-19 concerns may have been a stimulus to activate couples’ stress management processes. A couple’s resource, which may have an important role in dealing with COVID-19 concerns and stress, is dyadic coping, i.e., the process through which partners face stress together. Drawing on a sample of 1823 Italian individuals involved in a couple relationship, the current study tested a serial mediation model in which concerns about the COVID-19 predicted psychological well-being, through both explicit stress communication and perceived partner dyadic coping responses. In addition, the study explored whether this dyadic coping process functioned the same way in satisfied and dissatisfied couples. Results showed that concerns about the situation related to COVID-19 significantly threatened individuals’ psychological well-being. However, these concerns positively predicted explicit stress communication, which in turn positively predicted perceived partner’s dyadic coping responses, which finally positively predicted psychological well-being. In addition, in the group of dissatisfied individuals, the association between explicit stress communication and perceived partners’ dyadic coping responses was not significant. The present study adds to the research on couples’ coping by testing for the first time the whole theoretical model of dyadic coping and does so during a global emergency situation. The study also suggests key components of preventive interventions for individuals in couples.